Physiological and psychological health benefits of urban green space - Mohamed Mokhtar, Mohamed Daniel (2017)
This study explores the physiological and psychological effects of urban green space by using stress as a determinant of well-being. This study also aims to provide scientific evidence supporting the use of urban green space as a method to relieve stress. The subjects of this study were 20 male students which their homogeneity was controlled. The study area chosen for this study was Taman Botani Perdana, Kuala Lumpur and Jalan Bukit Bintang was used as a control area. The first day the participants went to Taman Botani Perdana and on the second day to Jalan Bukit Bintang. Participants were asked to walk along a given route in both areas in which the time was set similarly in both areas (20 minutes). Saliva samples were collected before and after walking in both areas along with blood pressure measurements. In addition, psychometric tests namely the Profile of Mood States (POMS), Positive and Negative Affect Schedule (PANAS), Perceived Stress Scale (PSS) and the Restoration Outcome Scale were done to identify the psychological effects of urban green space use. The results indicated that salivary cortisol concentration levels among participants in the urban green space is significantly lower than the participants in the city. Blood pressure readings also showed a significant decrease in value among participants in UGS for diastolic pressure. In the Restoration Outcome Scale (ROS), participants in the UGS setting reported a higher score for all six statements in the scale compared to the City setting with a significance of p < 0.01. The POMS test indicated a clear distinction between the restorative effects of urban green space and city as the Total Mood Disturbance (TMD) of participants in the urban green space showed negative in value while participants in the city showed positive TMD. Perceived Stress scores in the urban green space is significantly higher in mean value compared to the city setting in both before and after period. When summing the scores of positive and negative subscales of the PANAS test, a significant difference can be found at the city setting for both positive and negative subscales. Positive attitudes decreased while negative attitudes increased after walking in the city. In the UGS setting however, only positive attitudes increased.